2020
DOI: 10.1038/s41598-020-67971-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phenylalanine and glutamine concentrations correlate with subsequent hepatocellular carcinoma occurrence in liver cirrhosis patients: an exploratory study

Abstract: Aberrant metabolisms have been hypothesized to precede the occurrence of hepatocellular carcinoma (HCC), therefore, we investigated biomarkers associated with subsequent HCC in peripheral bloods using metabolomic technologies. A cohort of 475 HCC-naïve liver cirrhotic patients were recruited and prospectively followed. A total of 39 patients developed HCC in the follow-up period. Baseline plasma metabolites were explored using untargeted nuclear magnetic resonance. candidates were then quantified by ultra-perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…This observation is consistent with the decrease in glutamate observed in our study, in view of the metabolic links between these two amino acids. The dysregulation of this pathway has been observed in another cohort study [22] and other types of cancers as well, such as in breast cancer [56] and in hepatocellular carcinoma (HCC) [57].…”
Section: Discussionmentioning
confidence: 91%
“…This observation is consistent with the decrease in glutamate observed in our study, in view of the metabolic links between these two amino acids. The dysregulation of this pathway has been observed in another cohort study [22] and other types of cancers as well, such as in breast cancer [56] and in hepatocellular carcinoma (HCC) [57].…”
Section: Discussionmentioning
confidence: 91%
“…Phenylalanine in the peripheral blood was elevated in HCC patients compared with that in liver cirrhosis patients. 27 Liang et al 28 concluded that age, plasma phenylalanine, and glutamine concentrations altogether offered a risk score that was correlated with subsequent HCC occurrence in liver cirrhosis patients. In the present study, an increased serum phenylalanine level suggested a more serious impaired liver function in HCC patients than in CHB patients, because the liver is the major organ where phenylalanine is mainly metabolized.…”
Section: Discussionmentioning
confidence: 99%
“…L-phenylalanine and enol-phenylpyruvate are metabolites of phenylalanine metabolism. L-phenylalanine has been reported to be positively correlated with imaging findings in liver injury patients and progression in liver cirrhosis patients ( 21 , 22 ). A recent study reported that L-phenylalanine and phenylpyruvate via glycolysis inhibition affect energy metabolism of hepatocytes ( 23 ).…”
Section: Discussionmentioning
confidence: 99%